1998
DOI: 10.1111/j.2044-8279.1998.tb01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Affective variables, learning approaches and academic achievement: a causal modelling investigation with Hong Kong tertiary students

Abstract: Background. Academic learning outcomes are believed to be influenced by a complex system that involves the interaction of student personality characteristics and learning processes. Yet to date there have been few studies, particularly in a non-western culture, which have examined the interrelationships between these variables and their causal effects on achievement outcomes.Aims. This study aims to investigate the interrelationships of affective variables, learning approaches and academic achievement. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 45 publications
9
45
1
4
Order By: Relevance
“…In a study to investigate the relationship between self-beliefs, academic background and achievement of adolescent Asian-American students in postsecondary education (House, 1997), academic self-concept was found to be a significant predictor of Asian-American students' subsequent academic performance. In another study (Drew & Watkins, 1998) academic self-concept was found to be directly and significantly related to the deep rather than the surface learning approach. This is probably because when a learner has a positive concept of his academic ability he is more confident in his ability and his motivation becomes intrinsic (Drew & Watkins, 1998).…”
Section: Bmentioning
confidence: 99%
“…In a study to investigate the relationship between self-beliefs, academic background and achievement of adolescent Asian-American students in postsecondary education (House, 1997), academic self-concept was found to be a significant predictor of Asian-American students' subsequent academic performance. In another study (Drew & Watkins, 1998) academic self-concept was found to be directly and significantly related to the deep rather than the surface learning approach. This is probably because when a learner has a positive concept of his academic ability he is more confident in his ability and his motivation becomes intrinsic (Drew & Watkins, 1998).…”
Section: Bmentioning
confidence: 99%
“…In a study to investigate the relationship between self-beliefs, academic background and achievement of adolescent AsianAmerican students in post-secondary education (House 1997), academic self-concept was found to be a significant predictor of Asian-American students' subsequent academic performance. In another study, academic self-concept was found to be directly and significantly related to the deep rather than the surface learning approach (Drew and Watkins 1998).…”
Section: Discussionmentioning
confidence: 99%
“…According to Drew and Watkins (1998), self-concept is a psychological construct which refers to a cluster of ideas and attitudes an individual holds about himself/herself. Mwamwenda (1995) regards self-concept as a person's way of perceiving himself/herself and may be either positive or negative.…”
Section: Academic Self-conceptmentioning
confidence: 99%
“…Economic, social and cultural factors also have an important role to play in determining academic performance at an undergraduate level. However, the socio-economic factors that affected one's performance at an undergraduate level (in the above studies [3][4][5][6][7][8][9][10][11][12] ) may not be as strongly pronounced for an honours degree. Nevertheless, including these factors as covariates in our prediction model will be important for the analysis that follows.…”
Section: Research Articlementioning
confidence: 99%
“…Entry requirements and throughput rates for honours Page 2 of 6 successful they have been in coping with difficult situations they have encountered at university [10][11][12] . Economic, social and cultural factors also have an important role to play in determining academic performance at an undergraduate level.…”
Section: Research Articlementioning
confidence: 99%